Celostna rehabilitacija bolnikov po covidu-19 in respiratorni odpovedi – naše izkušnje - Oblak, Tina (Rehabilitacija (Ljubljana), 2024)
Introduction: Patients with severe COVID-19 infection may suffer from pneumonia with respiratory failure and consequent Post Intensive Care Syndrome (PICS) including Critical Illness Neuropathy (CIN) and Critical Illness Myopathy (CIM). The aim of our study was to evaluate rehabilitation outcome in these patients. Methods: Fifty patients (14 female, 36 male) with CIN or CIM as a consequence of COVID-19 and respiratory failure, who were admitted to the University Rehabilitation Institute, Republic of Slovenia, were included in the study. Patients’ activities were assessed using the Functional Independence Measure (FIM), 10 Metre Walk Test and 6-Minute Walk Test. Motor FIM gain was used to assess rehabilitation efficacy. Nutritional status was assessed using anthropometric measurements and Bioelectrical Impedance Analysis (BIA). Assessment was performed at admission and at discharge. Results: Average age at admission was 62 years. At admission, severe impairment of body functions with consequent activity and participation limitations were present in all patients. The duration of rehabilitation was approximately 6 weeks. Clinically important and statistically significant improvements were achieved regarding all observed variables (p < 0.001) At discharge, all patients were independent in activities of daily living. In addition, they were all able to walk, half of them without walking aid. Conclusion: Comprehensive multidisciplinary rehabilitation of patients after COVID-19 and respiratory failure patients was effective in our sample. In a relatively short period of rehabilitation, patients achieved important improvement in their activities.
Keywords: COVID-19; critical illness neuropathy and myopathy; dihalna odpoved; FIM; Functional Independence Measure; izid; lestvica funkcijske neodvisnosti; miopatija kritično bolnega; nevropatija; outcome; rehabilitacija; Rehabilitation; respiratory failure; testi hoje; walk tests